Interaction of laser light with biological specimens - Ng, Stanley Mong Seng. (2009)
Light distribution in tissues is a problem that has baffled researchers of laser therapy. With the increased popularity of photodynamic therapy to treat certain tumours, the understanding of the light distribution in tissues becomes increasingly important. It is known that the light distribution in a tissue is governed by the absorption coefficient, ua, scattering coefficient, us, and the anisotropy coefficient, g. Work has been done by many researchers to develop models to map light distribution in tissues in order to better understand its behaviour.